2020
DOI: 10.1007/s43390-020-00165-7
|View full text |Cite
|
Sign up to set email alerts
|

Major complications following surgical correction of spine deformity in 257 patients with cerebral palsy

Abstract: Study design Observational. Objectives To report on the rate of major complications following spinal fusion and instrumentation to treat spinal deformity in patients with cerebral palsy (CP). Summary of background data Understanding the risk of major complications following the surgical treatment of spine deformities in patients with CP is critical. Methods A prospectively collected, multicenter database of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
25
1
Order By: Relevance
“…There were several years in which NM patients had a higher mortality rate than the other kyphosis group (2016-2017, 2019-2020). In their prospectively collected, multicenter database in cerebral palsy patients treated surgically, Yaszay et al found that 11 of 257 (4.3%) patients died between 3 months and 5.6 years postoperatively [17]. In addition, 4 (1.5%) patients died less than a year after surgery and 2 (0.7%) deaths were directly related to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There were several years in which NM patients had a higher mortality rate than the other kyphosis group (2016-2017, 2019-2020). In their prospectively collected, multicenter database in cerebral palsy patients treated surgically, Yaszay et al found that 11 of 257 (4.3%) patients died between 3 months and 5.6 years postoperatively [17]. In addition, 4 (1.5%) patients died less than a year after surgery and 2 (0.7%) deaths were directly related to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis correction surgery is a procedure associated with high risks as reported by numerous studies; pulmonary complications being the most common [9][10][11][12]. Patients suffering from a neuromuscular disorder e.g.…”
Section: Discussionmentioning
confidence: 99%
“…All of the mentioned factors along with the long duration of the surgery can influence the frequency and severity of postoperative complications [8]. Studies conducted with regard to the complications of correctional surgery of NMS have showcased similar complication rates, especially pulmonary complications [9][10][11][12]. One retrospective study conducted by Luhmann and Furdock found that the highest postoperative complications were pulmonary complications with a rate of 15.3% among 111 NMS patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…CSM surgery for patients with CP remains challenging because of perioperative instrumentation failure caused by the patient’s repetitive involuntary neck movements, complicated cervical spine deformities, and comorbidities. Several studies have reported postoperative complications in patients with CSM without CP or scoliosis with CP [ 24 , 33 ]. However, there exist only a few reports regarding postoperative complications in patients with CSM and CP.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, complication rates in NCP patients who underwent cervical surgery due to CSM were 9–30% [ 17 , 23 , 26 , 31 ]. Yaszay et al [ 33 ] reported a rate of 36% for postoperative major complications (e.g., wound infections, pulmonary issues, instrument-related complications) in patients with CP with >2 years of follow-up after spinal surgery, with a spine-related reoperation rate of 14.0%. Samdani et al [ 24 ] reported a 39% complication rate in 127 patients with CP who underwent spinal surgery.…”
Section: Discussionmentioning
confidence: 99%